2000
DOI: 10.1002/1097-4652(200011)185:2<244::aid-jcp9>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of three glucose transporter genes in a renal epithelial cell line

Abstract: Three hexose transporter genes, the Na(+)/glucose cotransporters SGLT1 and SGLT3 (formerly SAAT1/pSGLT2) and the facilitative transporter GLUT1, are expressed in a renal epithelial cell line with proximal tubule characteristics. A number of studies have demonstrated that SGLT1 expression is coupled to the cellular differentiation state and is also negatively regulated by its substrate glucose. In the present study, we demonstrate that SGLT3 mRNA expression is relatively unaffected by conditions promoting dedif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Indeed the observed inhibition of α‐MG uptake caused by a combination of EGF and H 2 O 2 was completely reversed by PD 98059 and mepacrine. Thus, our results indicate the involvement of the p44/42 MAPK pathway, which lies at the heart of many signal transduction processes and constitutes a major pathway through which growth factors transduce signals to the nucleus following their interaction with specific receptors (Chakraborti and Chakraborti, 1998; Clancey and Lever, 2000; Kolch, 2000).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Indeed the observed inhibition of α‐MG uptake caused by a combination of EGF and H 2 O 2 was completely reversed by PD 98059 and mepacrine. Thus, our results indicate the involvement of the p44/42 MAPK pathway, which lies at the heart of many signal transduction processes and constitutes a major pathway through which growth factors transduce signals to the nucleus following their interaction with specific receptors (Chakraborti and Chakraborti, 1998; Clancey and Lever, 2000; Kolch, 2000).…”
Section: Discussionmentioning
confidence: 70%
“…Apically localized Na + /glucose cotransporters in the renal proximal tubule play a central role in the reabsorption of glucose from the glomerular filtrate by mediating the transport of glucose into renal proximal tubule cells (PTCs). Subsequently, efflux of accumulated intracellular glucose occurs by means of facilitated diffusion systems for glucose localized in the basolateral membrane (Clancey and Lever, 2000; Wright, 2001). During instances of where filtered glucose is incompletely reabsorbed, a consequence is osmotic effects, which disrupt normal fluid and electrolyte homeostasis, as exemplified in poorly controlled diabetic mellitus (Oku et al, 2000).…”
mentioning
confidence: 99%
“…18,19 SGLT1 is an apical site transporter and its mRNA expression is observed just after confluence is reached. 18,19 SGLT1 expression is associated with cellular differentiation. 19 In the present study, we demonstrated that SGLT1 mRNA expression was maintained for 3 weeks after the cells reached confluency, regardless of overconfluency (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…GLUT1 mRNA is expressed during the growth and differentiation phases. 18,19 SGLT1 is an apical site transporter and its mRNA expression is observed just after confluence is reached. 18,19 SGLT1 expression is associated with cellular differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation